Coloniality and extractivism: is there a right to an ecologically balanced environment? (PerCursos, 2023)
The purpose of this article is to highlight some of the contributions of decolonial thought to examining the connection between extractivism and colonialism. This approach enables us to grasp the distinct aspects that extractivism takes on in the context of modernity. Consequently, the article is structured into three main sections. First, it introduces the foundations of decolonial thought and the concept of the coloniality of nature. Second, it explores the link between modern philosophy and the exploitation of nature. Third, it critically examines the myth of development. The methodology employed in this study is a literature review.
Keywords: coloniality; extractivism; exploration of nature